Hibridação cultural e educação ambiental: memórias de uma comunidade rural de Uberlândia - Dias, Inez Reptton (2012)
This research paper deals with the idea of how environment can be associated to cultural issues, and the way popular knowledge on Cerrado plants can be worked on environmental education proposals. Considering the wealth of cultural hybridization processes, and their linking with that knowledge, memories of a rural community regarding its members‟ traditions and life experience were sought and registered in a documentary. To understand how the inhabitants of that community get to know their own culture and their relationship with the environment, the students of its municipal school were proposed to make a photographic record of the local. The narratives and pictures produced throughout the research show that the community culture is inserted in a hybridized context, once both the knowledge acquired by the inhabitants‟ life experience and the scientific resources characterize their way of life. This condition can be verified especially by the testimony of the plant experts for the documentary about the recovery of ancient customs and traditions in parallel with acceptance of modernity. Valuing the media language presented by the pictures and videos has allowed an interaction between the pants experts and the students at the divulgation of the cultural-historic relation established by the community with the environment.